Impact of public sector talent retention on brain drain in selected north-central states in Nigeria - Ali Yakubu; Hassan Achimugu; Ata-Agboni Joy Uyo (Southeast Asian Journal of Service Management, 2026)
There is paucity of studies that examined whether Public Sector Talent Retention has effect on the problem of Brain Drain in North-Central States in Nigeria. This study bridges that gap by asking whether Public Sector Talent Retention has effect on brain drain in Nigeria. It also asks pertinent questions with a view to digging deep into the possible causes of labour mobility. This study examines the relationship between public sector talent retention strategies and brain-drain issues in North-Central states through a quantitative empirical analysis. Brain drain has emerged as a significant threat to Nigeria's socio-economic development, with approximately half of licensed medical doctors and substantial numbers of academic professionals migrating to developed countries. This study adopted a quantitative, cross-sectional survey research design. This study collected data from 705 public sector employees across the North-Central States and employed structural equation modeling (SEM) and multiple regression analysis to examine the relationship between talent retention practices and brain drain mitigation. Findings reveal that career development opportunities emerged as the strongest predictor of brain drain intentions (β = -0.298, p < 0.001), followed by compensation satisfaction (β = -0.271, p < 0.001). Poor working conditions, limited career advancement opportunities, and insufficient professional development programs significantly contribute to brain drain intentions among public sector professionals. The Federal, States, Local Government and private employers of labour need to start implementing competitive remuneration packages, improving workplace infrastructure, creating clear career progression pathways and establishing robust professional development programs to enhance talent retention in Nigeria's public sector. Among the few studies that examined the effect of Public Sector Talent Retention on Brain Drain, basically, none covers North-Central States of Nigeria except this which gives the study its originality. The study contributes to the existing body of knowledge by providing empirical evidence on the relationship among talent retention and brain drain in Northern Nigeria. The theoretical framework is anchored on Herzberg's Two-Factor Theory of motivation and Human Capital Theory.